Tax Audit and Collection on Tax Revenue - Jamian Purba; Dian Sulistyorini Wulandari; Neng Deti Rohimah (East Asian Journal of Multidisciplinary Research, 2023)
This study aims to determine the effect of tax audits and collections on tax receipts at the South Cikarang Pratama Tax Service Office. The research method used in this study is quantitative. The data used is secondary data in the form of payment performance reports and tax revenue performance reports at KPP Pratama Cikarang Selatan. The sampling technique used in this study was the convenience sampling method. The measurement scale used in the time series is the ratio scale. To determine the accuracy of the data, the analysis technique used in this study is multiple linear regression analysis. The results of the analysis show that tax audits have a positive and significant effect on tax revenues, and tax collection has a negative and significant effect on tax revenues.